In our midst : a novel - Jensen, Nancy, 1961- (Dzanc Books, 2020)
"Drawing upon a long-suppressed episode in American history, when thousands of German immigrants were rounded up and interned following the attack on Pearl Harbor, In Our Midst tells the story of one family's fight to cling to the ideals of freedom and opportunity that brought them to America. Nina and Otto Aust, along with their teenage sons, feel the foundation of their American lives crumbling when, in the middle of the annual St. Nikolas Day celebration in the Aust Family Restaurant, their most loyal customers, one after another, turn their faces away and leave without a word. The next morning, two FBI agents seize Nina by order of the president, and the restaurant is ransacked in a search for evidence of German collusion. Ripped from their sons and from each other, Nina and Otto are forced to weigh increasingly bitter choices to stay together and stay alive. Recalling a forgotten chapter in history, In Our Midst illuminates a nation gripped by suspicion, fear, and hatred strong enough to threaten all bonds of love--for friends, family, community, and country."--Provided by publisher.